Front Cover: Cs3Na(H2C3N3O3)4·3H2O: A Mixed Alkali‐Metal Hydroisocyanurate Nonlinear Optical Material Containing π‐Conjugated Six‐Membered‐Ring Units (Eur. J. Inorg. Chem. 23/2019). Issue 23 (6th June 2019) - Meng, Xianghe; Liang, Fei; Tang, Jian; Kang, Kaijin; Huang, Qian; Yin, Wenlong; Lin, Zheshuai; Xia, Mingjun
Abstract : The Front Cover shows the characteristics of the title compound, including the conjugation of the (H2 C3 N3 O3 ) – six‐membered ring units (top left corner) as well as the two‐dimensional layered structure composed of the large, coplanar, π‐conjugated 2 ∞ [H2 C3 N3 O3 ] – isocyanurate ribbons (in the largest bubble in the middle), and the nonlinear optical properties of the crystal. The bubbles indicate that the reaction is carried out in aqueous solution. More information can be found in the Communication by W. Yin, M. Xia et al. For more on the story behind the cover research, see the Cover Profile .